Challenges And Strategic Roles of Philology And Manuscripts In Building Islamic Civilization In The Contemporary Era - Hidayat, Roch Aris (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Islamic civilization has made significant contributions to the formation of global intellectual traditions through the development of language, literature, science, and educational systems. Language and literature serve not only as a medium of communication but also as instruments for transmitting values, knowledge, and civilizational identity. In the contemporary context, the study of Islamic manuscripts and philology has become increasingly important for tracing the dynamics of the history of thought, intellectual networks, and cultural transformations that have occurred across regions and eras. However, modern challenges such as the physical degradation of manuscripts, limited cataloging, minimal digitization, low regeneration of philologists, and the dominance of pragmatic approaches in education have put this intellectual heritage at risk of being marginalized. This article aims to explore how manuscripts and philological studies can bridge the gap between reading the history of Islamic civilization and formulating a more inclusive, tradition-rooted future. Through a qualitative-descriptive approach and literature study, this research demonstrates that manuscripts not only preserve historical records but also contain ethics, cosmologies, educational models, and social adaptation strategies relevant to addressing contemporary global problems. Philology, in this case, functions as a method of textual criticism and an instrument for revitalizing local and global knowledge. Thus, strengthening manuscript and philological studies is a strategic step in rebuilding historical awareness, enriching the intellectual treasury of Islam, and shaping the future direction of a dialogical, sustainable, and humanistic civilization.